The burial vault of the Dental College of Havana in Colon Cemetery - Alain Manuel Chaple Gil; Lisandra Quintana Muñoz; Josefa Dolores Miranda Tarragó (Editorial Ciencias Médicas, 2019)
Funerary monuments containing several tombs are called burial vaults. The purpose of the study was to describe some historical elements of the burial vault of the Dental College of Havana in Colon Cemetery. A historical-particular-descriptive study was conducted from June to December 2017. A review was performed of documents related to the topic in Colon Cemetery. The information obtained was arranged chronologically to facilitate the description of events related to the burial vault, and a search was carried out on the Internet and libraries to clarify the definitions and find similar research studies. All the information was scanned in a library created on EndNote X7 to facilitate the processing of the text in Microsoft Word. The burial vault was sold to the Dental College of Havana on 21 April 1939 as a parcel of land in Colon Cemetery. It is located in the South-West Quarter, Lot No. 6 of the Third Class Monuments Area, and carries the number 22361. Burials in the vault started on 14 January 1940, and the marble used for its construction was supplied by "Mármoles Pennino".